2009
DOI: 10.1002/mnfr.200900039
|View full text |Cite
|
Sign up to set email alerts
|

Tannins: Current knowledge of food sources, intake, bioavailability and biological effects

Abstract: Tannins are a unique group of phenolic metabolites with molecular weights between 500 and 30 000 Da, which are widely distributed in almost all plant foods and beverages. Proanthocyanidins and hydrolysable tannins are the two major groups of these bioactive compounds, but complex tannins containing structural elements of both groups and specific tannins in marine brown algae have also been described. Most literature data on food tannins refer only to oligomeric compounds that are extracted with aqueous‐organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
528
1
19

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 672 publications
(552 citation statements)
references
References 207 publications
(161 reference statements)
4
528
1
19
Order By: Relevance
“…It has been reported that pure polyphenols present antimicrobial activity against Gram-positive and Gram-negative bacteria (Puupponen-Pimiä et al, 2001;Serrano et al, 2009;Prado et al, 2014). Their mechanisms of action are related to oxidation of microbial cell membranes, complexation of essential metal ions, or inhibition of extracellular enzymes (Scalbert, 1991;Serrano et al, 2009). Lou et al (2012) reported that p-coumaric acid acts on altering the permeability of the cell membrane of Gran-negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that pure polyphenols present antimicrobial activity against Gram-positive and Gram-negative bacteria (Puupponen-Pimiä et al, 2001;Serrano et al, 2009;Prado et al, 2014). Their mechanisms of action are related to oxidation of microbial cell membranes, complexation of essential metal ions, or inhibition of extracellular enzymes (Scalbert, 1991;Serrano et al, 2009). Lou et al (2012) reported that p-coumaric acid acts on altering the permeability of the cell membrane of Gran-negative bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, some fungi such as A. niger and Penicillium sp. can grow in the presence of tannins, using these compounds as a carbon source or due to production of polyphenol hydrolyzing enzymes (Scalbert, 1991;Serrano et al, 2009). Figure 1 shows the results for antimicrobial activity of pecan nutshell extract against yeast, mesophilic and psychrotrophic bacteria in lettuce leaves stored for 5 days at refrigeration temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In general, higher degree of tannins diversity has been observed in vegetative parts when compared to the reproductive parts. Maximum number (10) of tannins has been observed in flowers and seeds followed by leaves (9). …”
Section: Resultsmentioning
confidence: 99%
“…In particular, the tannin containing remedies are in use as antihelmintics [5], antioxidants [6], anti-microbials and anti-virals [7], and for the cancer treatment [8]. Tannins are widely distributed in almost all plant foods [9,10]. However, the primary source of tannins as active pharmaceutical ingredients are the medicinal plants while the polyphenolic compounds themselves are not always well characterized and there exist differences in polyphenol composition among various plant species [11].…”
Section: Introductionmentioning
confidence: 99%
“…They nearly always occur together in plants. Due to the large number of references dealing with the oligomers, the proanthocyanidins will be discussed in a further overview of the COST action 926 [198].…”
Section: Summary: Monomeric Flavanols (Catechins)mentioning
confidence: 99%